A theological appraisal of the book of Malachi - Snyman, Fanie (Old Testament essays, 2014)
The central question put in this paper is: what is the contribution Malachi makes to a theological appreciation of the OT? Four dimensions in determining the theology of the book of Malachi have been detected: a theological dimension portraying the God active in the book, a cultic dimension emphasising the way in which YHWH demands to be worshipped; an ethical dimension highlighting the expected behaviour of the people of God and finally an eschatological dimension opening up a vision of a future to come.